Design of Single Stage Axial Turbine for Mini Turbojet Engine - I Syarafina; P Adnan; F Hartono (Institut Teknologi Bandung, 2020)
This paper explains about aerodynamic design of a single stage gas generator turbine for a small turbojet engine. The design requirement is that the turbine must be able to deliver power output of 150 kW at 0.814 kg/s gas mass flow, with turbine inlet temperature of 1200 K, and turbine inlet pressure of 267508 Pa. The design phase consists of 4 steps, which is thermodynamic property analysis using parametric cycle analysis, determination of velocity triangle in 2D plane and 2D blade design using CASCADE software, 3D geometry modeling, and 3D flow analysis at design point using Computational Fluid Dynamics method. In parametric cycle analysis, design points are applied to get the unknown thermodynamics property. The determination of velocity triangles, two conditions are applied: zero inlet swirl and constant nozzle angle design. The design continues with the 2D approach in CASCADE to determine the airfoil type at the hub, mean, and the tip of the blade based on the inlet and outlet flow conditions. The 3D approach flow analysis is done by simulating the 3D geometry that has been made using CAD in full configuration to evaluate the overall performance of the turbine, especially the power generated by the turbine. The observed parameters are clearance, stagger angle, and cambered flat plate substitution in NGV affects the turbine’s output power. The analysis results show that all of those parameters above affect the turbine’s output power in a different way from one to each other. The bigger the clearance, the power output and the efficiency that is generated by the turbine also become bigger. Same as clearance, the stagger angle of turbine’s NGV also affects the turbine power and efficiency. The bigger the stagger angle, the bigger the power, but the efficiency drops.